Cross‐sectional association between physical strength, obesity, periodontitis and number of teeth in a general population. (6th April 2016) - Eremenko, Michael; Pink, Christiane; Biffar, Reiner; Schmidt, Carsten O.; Ittermann, Till; Kocher, Thomas; Meisel, Peter
Abstract: Aim: Muscle strength declines and gums recede with increasing age across the life course. Possible associations exist between handgrip strength as an indicator of physical fitness and periodontitis and number of teeth. Material and Methods: Handgrip strength (GS), anthropometric measures, clinical attachment loss, number of teeth, C‐reactive protein and glycated haemoglobin were assessed in 2089 participants of the Study of Health in Pomerania (SHIP‐2). Linear regression including interaction with age was used to estimate the association between clinical attachment level, number of teeth and GS. Results: In multiple regression adjusted for age, body mass index (BMI) and waist‐to‐hip ratio (WHR) each mm of diminished periodontal attachment was associated with reduction in GS by 1.47 kg (95% CI −2.29 to −0.65) and 0.38 kg (−0.89 to 0.14) in men and women respectively. Correspondingly, each additional remaining tooth was significantly associated with higher GS. Using handgrip strength relative to BMI as outcome, these relationships become even more apparent. Indicators of obesity such as BMI and WHR associated with both GS and periodontitis modulate the relationship between GS and periodontitis with a different impact between the sexes. Conclusion: Periodontitis is associated with GS modified mainly by anthropometric measures related to adiposity and inflammation. Putative mechanisms encompass interactions of factors declining with increasing age.